Future Directions - Charalambous, Andreas (My University, 2023)
Future projections pointed to the direction that the persons who will be needing support by the healthcare systems will be well over their capacity. The increasing demand for care will place many more responsibilities on those who will be assuming the role of the informal caregiver. Over the years, informal caregivers have become an integral part of the care however without the appropriate recognition or support by the healthcare systems. This chapter provides an overview of the various models of informal caregivers’ involvement in care and how these can be chosen according to the needs of those on the receiving end of the care as well as the needs of the informal caregivers. The model of choice will also de depended on its exact purpose as well as the context where it will be implemented. The chapter continues with the discussion of the ways to support the role of the caregiver. Taking into consideration the fact that this role is highly demanding and complex, the support to be provided needs to be of equally extensive level. Finally, the chapter takes a look at the policy strategy that needs to be put in place in order to support informal caregiving over time.
Keywords: Hidden role; Caregiving models; Caregiving role; Informal care; Policy